Filling the legal vacuum in combatting maritime crimes: A law reform strategy for Malaysia - Hamid, Abdul Ghafur@Khin Maung Sein (Inderscience Publishers, 2017)
Maritime security is a major concern for Malaysia as a maritime nation. The crucial question nevertheless is whether there are adequate laws to deal with key maritime crimes that need effective law enforcement measures. The paper finds that no maritime offences are criminalized in the Penal Code, the principal criminal law of Malaysia and that there is neither an anti-piracy law nor any other special criminal law available in Malaysia to combat maritime crimes. A regretful failure to apply a more appropriate law to prosecute Somali pirates demonstrates well an urgent need in Malaysia for a law reform that can effectively combat maritime crimes. On the basis of an analysis of the laws of selected common law countries, the paper concludes with suggestions on proposed maritime crimes law to be recommended to the Government of Malaysia.